MOLECULAR ANALYSIS OF HEXON AND FIBER GENES OF FOWL AVIADENOVIRUSES ISOLATED FROM FIELD CASES OF INCLUSION BODY HEPATITIS - M. H.A. Mohamed; I. M. El-Sabagh (Journal of Animal and Plant Sciences, 2023)
Inclusion body hepatitis (IBH) is an infectious viral disease caused by fowl aviadenoviruses (FAdVs) leading to a significant economic losses in broilers in Saudi Arabia and worldwide. In this study, the FAdVs causing IBH were identified using the polymerase chain reaction (PCR) with primers directing the hexon gene. For a detailed molecular characterization, the complete open reading frames (ORFs) of hexon and fiber 2 genes were amplified and sequenced. The generated sequences were aligned and analyzed with certain FAdV reference strains. Five FAdV-D were detected had an average percentage of identity of approximately 96.80%. The detailed molecular analysis of the hyper-variable regions (HVRs) in the hexon loop 1 region revealed several amino acid substitutions that might alter the antigenicity as shown by an antigenic index analysis. The comparison of the genomic sequences of the fiber genes confirmed a 17‒amino acid deletion in the shafts of three investigated strains isolated during 2017-18. Several amino acid substitutions were reported in the fiber gene knob and tail regions. Based on fiber gene sequence analysis, the average percentage of identity of the investigated strains and certain FAdV-D reference strains was 94.24%. The frequent isolation and identification of FAdV-Ds in IBH clinical cases with an average genetic diversity of 56.10% when compared with reference strains of FAdV-C emphasize that current preventive measures should be reviewed and that a new homologous vaccine may be needed.
Keywords: IBH; Hexon gene; Fiber gene; Phylogenetic analysis; Fowl aviadenoviruses